Cowboy True: 2 Novels - Maggie's Dad and Champagne Girl - Palmer, Diana; Palmer, Diana (Toronto, Ontario HQN, 2021)
Rancher Big John Jacobs offers a marriage of convenience to the sheltered heiress of a railroad tycoon in "The Founding Father," and in "Justin," a man grieving over a broken engagement is reunited with his former fiancée.
The founding father -- Justin.
First work originally published in : A hero's kiss. New York : Harlequin, 2003. 2nd work originally published: New York : Harlequin, 1988.
Keywords: Romance; Fiction